Limnologische und systematische Studien an Ceratopogoniden (Diptera: Nematocera). - Havelka, Peter (Contributions to Entomology = Beiträge zur Entomologie, 1976)
Trapping huts were built over three books (Breitenbach, Btb; Rohrwiesenbach, Rwb; Kalkbach, Kb) in the Hessian Mountains near Schlitz. In the sections of the brooks that were examined a total of 75 species were established. Of these, 24 species, e. g. Ceratopogon gracilipes, Ceratopogon grandiforceps and Forcipomyia nigrans, were found for the first time in that area. Wing, antenna, palpus, mandible, spermatheca and hypophygium of all the species (exept the genus Culicoides) are illustrated and described with their morphological details. The distribution of the different species in the various geographical regions of Europe is shown. An occurrence of such species outside Europe, if known, is mentioned in the chapter on their distribution. The periods of the adult stage as given in previous publications are compared with those that were observed in this area. Finally a brief survey is given of each species with regard to its biology, preferred biotope or other interesting facts.